Effect of compatibilizers on in vitro biocompatibility of PLA–HA bioscaffold - Nainar S.M.M.; Begum S.; Ansari M.N.M.; Hoque M.E.; Aini S.S.; Ng M.H.; Ruszymah B.H.I. (Thomas Telford Services Ltd, 2023)
This paper exclusively describes the biocompatibility evaluation of biodegradable PLA–HA-based composites as temporary bone scaffolds for bone tissue engineering in orthopaedic applications. For that purpose, a set of composites were prepared using 3D melt-deposition method that comprises a biopolymer namely polylactic acid (PLA), and a bioceramic filler, namely hydroxyapatite (HA) 10 wt%, and compatibilizers, namely poly acrylic acid (PAA) 2 wt% and maleic anhydirde (MAH) 2 wt%. The composite samples were evaluated by in vitro assays and biodegradability tests were conducted in phosphate-buffered saline (PBS). For the in vitro analysis, osteogenic-induced stem cells were seeded onto the composite scaffold. An inverted optical microscope with computerised image analysis system was used to obtain data regarding cell attachment and contact characteristics after seeding for 48 h. Results showed that the PLA–HA-based composites did not induce adverse reactions from the cells, which in addition to their bone-matching mechanical properties makes them promising materials for bone scaffold applications. © 2014, Thomas Telford Services Ltd. All rights reserved.